The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1167/iovs.62.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-665-3p Enhances Autophagy and Alleviates Inflammation inFusarium solani-Induced Keratitis

Abstract: PURPOSE. Accumulated evidence has shown that microRNAs (miRNAs) are closely related with the regulation of autophagy, which plays vital roles in fungal keratitis (FK). Microarray data showed elevated expression of miR-665-3p in mouse corneal tissues after infection with Fusarium solani (F. solani). Here, we investigated the effect of miR-665-3p in regulating autophagy in experimental F. solani keratitis and determined the potential molecular mechanisms involved. METHODS. In this article, we established an in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…1 C). We further analyzed our previous results of a miR chip on mouse fungal keratitis 17 and displayed differentially expressed miRs between fungal keratitis and the control by a volcano plot (adjusted P ≤ 0.05, |log 2 Fold-change| ≥ 2) ( Fig. 1 D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 C). We further analyzed our previous results of a miR chip on mouse fungal keratitis 17 and displayed differentially expressed miRs between fungal keratitis and the control by a volcano plot (adjusted P ≤ 0.05, |log 2 Fold-change| ≥ 2) ( Fig. 1 D).…”
Section: Resultsmentioning
confidence: 99%
“… 18 Consistent with this, we also validated an increase of miR-223-3p level in a mouse model infected with F. solani . 17 At present, the precise function of miR-223-3p in FK is still vague.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Fusarium solani fungal keratitis (FK) mouse models, miR-223-3p might regulate autophagy via targeting ATG16L1 and was associated with the inflammatory response, which might be a potential therapeutic target [ 70 ]. Another study has demonstrated that the expression of miR-665-3p in the cornea was upregulated and autophagy flux was impaired when infected with Fusarium solani, thus miR-665-3p inhibitors might activate autophagic pathways and inhibit inflammation to cure FK [ 71 ]. The autophagy level in mice corneas increased after fumigatus infection, especially at 3 days.…”
Section: Research Progress Of Exosomes and Autophagy In Ocular Surfac...mentioning
confidence: 99%